Infiltrated Pr2NiO4 as promising bi-electrode for symmetrical solid oxide fuel cells. (3rd May 2018) - Gao, Zhipeng; Ding, Xifeng; Ding, Dong; Ding, Liming; Zhang, Shihua; Yuan, Guoliang
Abstract: In-situ growth of nanoparticles on electrode surface for high temperature energy conversion devices is one of efficient ways for new electro-catalyst design. Here, perovskite-related Pr2 NiO4 (PNO) has been evaluated as a novel symmetrical electrode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). Nickel nanoparticles are exsolved and dispersed on the surface of PNO after exposed in H2 at 800 °C as an efficient electrocatalyst for hydrogen oxidation reaction (HOR) as anode. The electro-activity towards oxygen reduction reaction (ORR) at cathode side is further improved by infiltration process. A synergetic effect of in - situ exsolved nanoparticles as well as infiltrated ionic conducting particles have improved HOR and ORR activity at anode and cathode side, respectively. Furthermore, symmetrical SOFC (SSOFC) with infiltrated Pr2 NiO4 as bi-electrode exhibits excellent short-term stability and reliable redox stability in repeated H2 /air cycles. Graphical abstract: Highlights: Pr2 NiO4 is developed as electrode material for symmetrical solid oxide fuel cells. Infiltration significantly promotes oxygen reduction reaction activity of Pr2 NiO4 . The composite electrode shows a polarization resistance of 0.061 Ω cm 2 at 800 °C. Maximum power density of a single symmetrical cell reaches 375 mA cm −2 at 800 °C.